A Challenging Case of a Large Gastroduodenal Artery Pseudoaneurysm after Surgery of a Peptic Ulcer - Rocio Santos-Rancaño; Esteban Martín Antona; José Vicente Méndez Montero (Case Reports in Surgery)
We report a 48-year-old man in whom a chronic postbulbar duodenal ulcer destroyed much of the back wall of the duodenum and gastroduodenal artery causing pseudoaneurysm. The lesion was found and evaluated by contrast-enhanced computed tomography (that revealed a large pseudoaneurysm of 83 mm × 75 mm in diameter) and by angiography and then treated with transcatheter embolization leading to a complete resolution of the lesion. The case is rare and important for several reasons. First, we demonstrate that pseudoaneurysm of the gastroduodenal artery caused by a duodenal ulcer can occur and present a diagnostic challenge (as far as we know, only three cases have been reported previously in the literature). Second, this case report focuses on the importance of ligation of the gastroduodenal artery when bleeding of peptic ulcers occurs. Additionally, we present an overview of the relevant literature.